2014
DOI: 10.5899/2014/ijcmb-00014
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Green Tea on IL-6 and CRP level in Model of Polycystic Ovary Syndrome as an Inflammation State

Abstract: Background: Having low-grade chronic inflammation state symptoms such as elevated C-reactive protein and interleukin-6 play a crucial role in polycystic ovary syndrome (PCOS). Green tea has antiinflammatory properties. This research evaluates the effect of green tea on inflammatory indexes. Adult Wistar rats were exposed to subcutaneous administration of estradiol valerate for PCOS induction. PCOS rats were divided into control and experimental groups received intraperitoneal injection green tea extract daily.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 48 publications
(47 reference statements)
2
19
1
Order By: Relevance
“…Green tea and green tea catechins have been shown to influence plasma levels of inflammation markers in several diseases that related to inflammation (Stote et al, 2012;Uchiyama et al, 2013;Fukuzawa et al, 2014). Ghafurniyan et al (2014) showed that intraperitoneal injection of green tea extract in Wistar rats with PCOS, caused significant reduction in CRP and IL-6 levels after 14 days, but this finding is not consistent with our results; however, this was an animal study. Also, Zolfaghary et al (2013) indicated that consumption of green tea extract (three-capsule extract for 12 weeks) led to significant reduction in CRP levels in obese women, which does not match with our study, and it was probably a result of the longer intervention period compared with our study.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Green tea and green tea catechins have been shown to influence plasma levels of inflammation markers in several diseases that related to inflammation (Stote et al, 2012;Uchiyama et al, 2013;Fukuzawa et al, 2014). Ghafurniyan et al (2014) showed that intraperitoneal injection of green tea extract in Wistar rats with PCOS, caused significant reduction in CRP and IL-6 levels after 14 days, but this finding is not consistent with our results; however, this was an animal study. Also, Zolfaghary et al (2013) indicated that consumption of green tea extract (three-capsule extract for 12 weeks) led to significant reduction in CRP levels in obese women, which does not match with our study, and it was probably a result of the longer intervention period compared with our study.…”
Section: Discussioncontrasting
confidence: 86%
“…Ghafurniyan et al . () showed that intraperitoneal injection of green tea extract in Wistar rats with PCOS, caused significant reduction in CRP and IL‐6 levels after 14 days, but this finding is not consistent with our results; however, this was an animal study. Also, Zolfaghary et al .…”
Section: Discussionmentioning
confidence: 94%
“… Ghafurniya et al 2015 [ 23 ] 96 Wistar rats were divided into 4 groups: PCOS group, three experimental groups, which were given 50, 100 and 200 mg/Kg BW green tea extract 10 days, intraperitoneally. 50,100,200 mg/kg/day GTE 10 day -LH serum level, body weight and ovarian weight decreased -Insulin resistance and blood glucose decreased -Improved of ovarian function Ghafurniya et al 2014 [ 24 ] 40 Wistar rats were divided into 5 groups: PCOS rats received no injections (PCOS control), rats received saline (sham), PCOS rats that received of 50 mg/kg of green tea extract (GT-Treated-1), rats that were received intraperitoneal injection 100 mg/kg of green tea extract (GT-Treated-2), rats that were received intraperitoneal injection 200 mg/kg of green tea extract (GT-Treated-3). 50,100,200 mg/kg/day GTE 2 weeks –CRP and IL-6 serum levels reduced.…”
Section: Resultsmentioning
confidence: 99%
“…Insulin resistance and hyperglycemia are the most common features of patients with PCOS [ 29 ]. In this regard, Ghafurniyan et al [ 24 ] reported positive effects of statistically significant from a 200 mg/kg injection of GTE for 10 days on insulin level in PCOS model rats [ 24 ]. Similarly, a statistically significant decrease in insulin resistance was reported after consumption of GTE in obese and overweight PCOS women ( P < 0.05) [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation